Acceptability and preferences for safer conception HIV prevention strategies: a qualitative study. (October 2016) - Schwartz, Sheree R; West, Nora; Phofa, Rebecca; Yende, Nompumelelo; Sanne, Ian; Bassett, Jean; Van Rie, Annelies
Safer conception strategies to reduce the HIV transmission risk include antiretroviral therapy for HIV-positive partners, pre-exposure prophylaxis for HIV-negative partners, condomless sex limited to fertile periods, and home-based self-insemination. Resistance to taking treatment or cultural concerns may limit uptake of strategies and intervention success. Understanding the acceptability and preferences between different approaches is important to optimise service delivery. Between February and July 2013, 42 adults (21 HIV-positive and 21 HIV-negative) receiving primary care at Witkoppen Health and Welfare Centre in Johannesburg, South Africa, participated in focus group discussions or in-depth interviews. Themes were analysed using a grounded theory approach. Acceptability of antiretroviral-based strategies varied. Concerns over side effects, antiretroviral treatment duration and beliefs that treatment is only for the sick were common barriers; however, desperation for a child was noted as a facilitator for uptake. HIV-negative men and HIV-positive women had favourable attitudes towards self-insemination, though paternity and safety concerns were raised. Self-insemination was generally preferred over pre-exposure prophylaxis by HIV-negative men, and antiretroviral-based strategies were preferred by couples with HIV-negative female partners, despite concerns raised about condomless sex while virally suppressed. Knowledge about the fertile window was low. A strong counselling component will be required for effective uptake and adherence to safer conception services.